2001
DOI: 10.1159/000048069
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Activation and Inactivation by Venom Proteases

Abstract: Blood coagulation factor V is a single-chain glycoprotein with Mr = 330,000 which plays an important role in the procoagulant and anticoagulant pathways. Thrombin activates factor V into factor Va, a two-chain molecule which is composed of a heavy (Mr = 105,000) and a light chain (Mr = 71,000/74,000). Factor Va accelerates factor Xa-catalysed prothrombin activation more than 1,000-fold and under physiological conditions the cofactor activity of factor Va in prothrombin activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…[12]. This SVTLE is able to activate factor V, a glycoprotein that plays an important role in the procoagulant and anticoagulant pathways [95], with a rate 250 -500-fold lower than thrombin ( fig. 4).…”
Section: Biological Properties Of Svtlementioning
confidence: 99%
“…[12]. This SVTLE is able to activate factor V, a glycoprotein that plays an important role in the procoagulant and anticoagulant pathways [95], with a rate 250 -500-fold lower than thrombin ( fig. 4).…”
Section: Biological Properties Of Svtlementioning
confidence: 99%
“…Some venom proteases also activate the protein cofactor, factor V. For example, RVV-V (Daboia russelli) and thrombocytin (Bothrops atrox) activate factor V, the cofactor in the prothrombinase complex (reviewed in [3,4] ).…”
Section: Procoagulant Proteasesmentioning
confidence: 99%
“…This latter activity was approximately 25-fold lower than the activating activity. This was concluded from the times required to obtain half-maximal activation of factor V and inactivation of factor Va in experiments that specifically probed the activation or inactivation of factor V(a) by LVV-V (Rosing et al, 2001). Simultaneous/consecutive activation and inactivation of coagulation factor V by venoms is not unique for LVV, as it was reported earlier that a commercial protein C activator from the venom of Deinagkistrodon contortrix contortrix can both activate and inactivate factors V and VIII (Gable et al, 1997).…”
Section: Other Viperidae Factor V Activatorsmentioning
confidence: 97%
“…Siigur and coworkers have purified and characterized the factor V activator from Vipera lebetina and have shown that this protease, like RVV-V, cleaves the factor V molecule at the Arg 1545 -Ser 1546 peptide bond (Siigur et al, 1998(Siigur et al, , 1999. In our laboratory, we compared the factor V activators from Daboia russelli, Vipera lebetina, and Vipera ursini, abbreviated RVV-V, LVV-V, and UVV-V, respectively (Rosing et al, 2001). The proteases have been purified to homogeneity (see Figure 5), and the apparent molecular weights determined were 29 kDa for V. lebetina and D. russelli and 34 kDa for V. ursini.…”
Section: Other Viperidae Factor V Activatorsmentioning
confidence: 99%